Natural biological control of African rice gall midge in Nigeria: IITA research guide, No. 37 - Umeh, E.D.N.; Joshi, R.; Ukwungwu, M.N. (1991)
The African rice gall midge (ARGM), Orseolia oryzivora Harris & Gagne, has recently emerged as an important insect pest of rice in many African countries. Infestation can result in total crop failure. Naturally occurring biological control agents have been identified in Nigeria that can reduce ARGM to tolerable levels. Researchers observed a large percentage of parasitized galls in unsprayed rice fields. Naturally occurring biological control agents attack ARGM population, thus reducing the severity and frequency of attack. Control agents reduce ARGM populations free of charge to the farmers. Natural enemies of ARGM in Nigeria so far discovered are parasitoids.